Nanoparticles loaded with natural medicines for the treatment of Alzheimer’s disease - Liu, Nanyang; Ruan, Juanjuan; Li, Hao; Fu, Jianhua (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease that disrupts cognitive function and severely affects the quality of life. Existing drugs only improve cognitive function and provide temporary relief of symptoms but do not stop or delay disease progression. Recently, natural medicines, especially Chinese herbal medicines, have gained attention in the treatment of AD due to their antioxidant, anti-inflammatory, and neuroprotective effects. However, conventional oral dosage forms lack brain specificity and have side effects that lead to poor patient compliance. Utilizing nanomedicine is a promising approach to improve brain specificity, bioavailability, and patient compliance. This review evaluates recent advances in the treatment of AD with nanoparticles containing various natural medicines. This review highlights that nanoparticles containing natural medicines are a promising strategy for the treatment of AD. It is believed that this technology can be translated into the clinic, thereby providing opportunities for AD patients to participate in social activities.